An empirical study on post divorce enforcement of court orders in Malaysia - Md Said, Muhamad Helmi; Mohd Zin, Najibah; Abdul Hak, Nora; Md Hashim, Noraini (IIUM Press, 2021)
This study investigates problems on the enforcement of court orders issued by the civil courts in divorce cases in Malaysia. Although the civil courts are guided by comprehensive statutory laws, however, issues on matters related to the enforcement of court orders especially maintenance orders are still unresolved. Therefore, this study is undertaken to examine and identify problems that have caused the failure to enforce these orders, post-divorce. A survey was conducted on one hundred and sixty-seven respondents came from five regions in Malaysia. The survey using questionnaires was the main method of collecting data. To support the empirical evidence, semi-structured interviews were also conducted in this study. The study discloses an obvious co-relation between complex and lengthy processes, unnecessary time consuming and costs inefficiency with the enforcement of orders after the divorce has taken place. This article is a prelude to a projected study on the enforcement of court orders issued by Civil Courts whereby the result will be useful for further improvement of the existing legal provisions in Malaysia.